Peran Sistem Tracking Digital Dalam Meningkatkan Akurasi Informasi Pengiriman Di J&T Express Cabang Mamuju - Heliska, Nur; Irfan; Hari yeni (Jurnal Ilmu Teknologi Informasi Indonesia, 2026)
This study aims to analyze the role of digital tracking systems in improving the accuracy of shipping information at J&T Express Mamuju Branch. Along with the growth of e-commerce, the accuracy of information has become a crucial factor for customer satisfaction and the competitive advantage of logistics companies. This study utilizes a qualitative descriptive method with data collection techniques including in-depth interviews, observation, and documentation. Key informants were selected using purposive sampling, consisting of management, operational staff, and customer service. The results indicate that the digital tracking system plays a strategic role as the primary means for recording and delivering real-time shipping information. Generally, the delivery status information generated by the system aligns with the actual condition of the packages in the field. However, the effectiveness of this system is not purely technologically deterministic but is heavily influenced by human and environmental factors. The findings identify that the discipline and precision of officers in updating data are the main determining factors of information accuracy. Additionally, technical obstacles such as limited internet network in the Mamuju region and high package volumes at certain times remain barriers to maintaining consistent data accuracy. This study concludes that optimizing information accuracy requires synergy between reliable technology, human resource competence, and the consistent implementation of standard operating procedures (SOP).